Análise de crescimento e produtividade de cultivares de arroz de terras altas dos tipos tradicional, intermediário e moderno - Felix Alvarez, Rita de Cassia; Costa Crusciol, Carlos Alexandre [UNESP]; Stephan Nascente, Adriano (FapUNIFESP (SciELO), 2012)
The growth analysis allows the characterization and understanding of the upland rice cultivars development. This study aimed at characterizing, by using the growth analysis, the physiological components and agronomic performance, as well as the differences among traditional, intermediate and modern upland rice cultivars. The experiment was conducted under upland rice conditions, favored by the use of supplementary irrigation. The experimental design was randomized blocks, with three treatments consisting of traditional (Caiapó), modern (Maravilha) and intermediate (BRS Primavera) cultivars and eight replications. The leaf area index (LAI), instantaneous growth rate (IGR), relative growth rate (RGR), net assimilation rate (NAR) and specific leaf area (SLA), as well as grain yield and yield components, were evaluated. The intermediate and traditional cultivars presented the highest total dry matter accumulation rate, while the traditional and modern ones showed the highest LAI. The intermediate cultivar presented the highest IGR, RGR, NAR and SLA levels, as well as the highest grain yield, as a consequence of the higher spikelet fertility and 1,000 grain mass.
Growth analysis and yield of traditional, intermediate and modern upland rice cultivars
Keywords: Leaf area index; Oryza sativa L.; Plant development; Plant physiological components